Whistling While They Work - Roberts, Peter (ANU Press, 2011)
This guide sets out results from four years of research into how public sector organisations can better fulfil their missions, maintain their integrity and value their employees by adopting a current best-practice approach to the management of whistleblowing. This guide focuses on: the processes needed for public employees and employees of public contractors to be able to report concerns about wrongdoing in public agencies and programs; and managerial responsibilities for the support, protection and management of those who make disclosures about wrongdoing, as part of an integrated management approach. The guide is designed to assist with the special systems needed for managing 'public interest' whistleblowing-where the suspected or alleged wrongdoing affects more than the personal or private interests of the person making the disclosure. As the guide explains, however, an integrated approach requires having good systems for managing all types of reported wrongdoing-including personal, employment and workplace grievances-not least because these might often be interrelated with 'public interest' matters.